PENERAPAN MODEL PEMBELAJARAN SCRAMBLE DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN PPKN - Baiq Yulia Rahmatul Asrianti; Edy Herianto; Sawaludin; Lalu Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine whether there is an effect of the application of the scramble learning model on student learning outcomes in Civics subjects at SMPN 1 Sikur. The approach used is quantitative, with the type of quasi-experiment research using one group pretest-posttest design. The population was all VIII grade students at SMPN 1 Sikur consisting of 7 classes and the sample taken was one class, namely class VIII E. The research sample technique used purposive sampling technique. Analysis of research data using prerequisite tests, namely normality test, homogeneity test and hypothesis test. The results showed that there was an effect of the application of the scramble learning model on student learning outcomes in Civics subjects. This can be proven in the acquisition of t count> t table = 52.667> 2.001